More for the Girls? Postindependence Education Expenditure in Timor-Leste - WISNU SETIADI NUGROHO; ANITA ALVES PENA (Asian Development Review)
Using the Timor-Leste Survey of Living Standards, we show that the household education spending on girls was higher than for boys in the period following independence. This pattern contrasts with that in the neighboring and politically interrelated country of Indonesia. We explore how religious differences and supply and demand features of private (relatively costly) Catholic schools across these countries relate to the dynamics of these policy-relevant educational gaps during the course of development in Timor-Leste.